2003
DOI: 10.1111/j.1756-1051.2003.tb00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in macroalgal communities along ferry routes in a northern Baltic archipelago

Abstract: Species composition, abundance and biomass of littoral macroalgae were studied along a ferry route in the and archipelago, northern Baltic Sea. Two areas, originally studied in the 1970s, were revisited in 1999 and 2000. In one area the traffic has strongly decreased since the 1970s, in the other the frequency of the traffic has remained the same, but the size of the ferries has increased. During the revisit the highest number of species was found close to the ferry route, in contrast to the results of the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…A likely explanation is the physical disturbance by boats, for example propeller scarring and damaging currents (Dawes et al 1997 ; Asplund and Cook 1999 ). Finally, the lower cover of filamentous algae in the marinas points towards a third possible mechanism; non- or loosely-attached species could be washed ashore or out of the inlets as a result of boat-generated wake and currents (Roos et al 2003 ). Here, a contributing factor could be the lower cover of rooted foundation species that act as substrate for these epiphytic algae.…”
Section: Discussionmentioning
confidence: 99%
“…A likely explanation is the physical disturbance by boats, for example propeller scarring and damaging currents (Dawes et al 1997 ; Asplund and Cook 1999 ). Finally, the lower cover of filamentous algae in the marinas points towards a third possible mechanism; non- or loosely-attached species could be washed ashore or out of the inlets as a result of boat-generated wake and currents (Roos et al 2003 ). Here, a contributing factor could be the lower cover of rooted foundation species that act as substrate for these epiphytic algae.…”
Section: Discussionmentioning
confidence: 99%
“…Rinne et al 2014, Virtanen et al 2018 have brought valuable spatial information on their potential distributional ranges, yet information on their actual abundances and their commonness across environmental gradients is largely lacking. For example, the abundances of red algae, known to form a zone below the Fucus belt (Waern 1952, Kiirikki 1996, Snoeijs 1999, Kostamo 2008, Kostamo et al 2017, , have been reported only in local studies (Häyrén 1950, Waern 1952, Ravanko 1968, Wallentinus 1979, Pogreboff & Rönnberg 1987, Bergström & Bergström 1999, Rönnberg & Mathiesen 1998, Roos et al 2003. Red algae occur generally in 2-10 m depth, but may reach 16-20 m depth (Kostamo 2008, Ruuskanen 2016).…”
Section: Rocky Shoresmentioning
confidence: 99%
“…Heavy waves can also dislodge perennial macroalgae and mussels. As reef species inhabit exposured coasts the wave action can also have positive effects as has been found on the routes of the larger car-ferries where water movements are strong and regular keeping the bottoms free from the sediments and drifting algae (Roos et al 2004). As increasing turbidity, wave action may have also effects on lower depth limit (Eriksson e al.…”
Section: Physical Disturbance (Appendix 1)mentioning
confidence: 99%